2014
DOI: 10.1111/jace.12790
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Transition and Low‐Temperature Dielectric Relaxations in Filled Tungsten Bronzes

Abstract: A comprehensive review on the latest development of the ferroelectric transition and low-temperature dielectric relaxations of filled tungsten bronze ceramics are presented together with some new issues. In the filled tungsten bronze ceramics M 6 -p R p Ti 2+p Nb 8 -p O 30 (p = 1, 2; M = Ba or Sr; R = rare earth or Bi), a ferroelectric transition is generally indicated together with up to three low-temperature dielectric relaxations. The ferroelectric transition is determined as 4/ mmm ? 4 mm, and the low-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 75 publications
1
58
0
Order By: Relevance
“…19,37,[64][65][66][67][68][69][70][71] However, the relaxor-like response in these is often subtle or convoluted with the main permittivity peak associated with T C and has not been demonstratively linked changes in the structural or P-E properties and so the origins of such behavior has not been convincingly assigned. The pronounced separation of the features presented here for Ba 4 La 0.67 !…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,37,[64][65][66][67][68][69][70][71] However, the relaxor-like response in these is often subtle or convoluted with the main permittivity peak associated with T C and has not been demonstratively linked changes in the structural or P-E properties and so the origins of such behavior has not been convincingly assigned. The pronounced separation of the features presented here for Ba 4 La 0.67 !…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that Chen and co-workers also proposed a model to predict relaxor vs. ferroelectric behavior but which considered only the difference in A-site cation radii. 37,39 As part of the proposed crystal-chemical framework 20 and in earlier 40 studies we reported the properties of a family of "empty" TTBs of general formula TTBs Ba 4 R 0.67…”
mentioning
confidence: 89%
“…One such case is presented in Figure 3 for Sr 5 SmTi 3 Nb 7 O 30 . In the context of this contribution, we note only that the complex interaction of multiple crystallographic sites with the incommensurate/commensurate modulation coupled to site disorder is likely to lead to so called 're-entrant' relaxor behavior, a topic dealt with by Zhu et al (2014). 54 However, the primary dielectric behavior discussed in this contribution is dominated by the average A-site ionic radius and the A1 tolerance factor, as illustrated in Figure 17.…”
Section: ) Crystal-chemical Frameworkmentioning
confidence: 97%
“…The tetragonal tungsten bronze structure is composed of ten distorted octahedral sharing corners in such a way that three different interstices (2 tetragonal A1, 4 pentagonal A2, and 4 triangle C) are available for cations in the general formula (A1) 2 (A2) 4 (C) 4 (B1) 2 (B2) 8 O 30 28 . In recent years, a number of Pb-free ferroelectrics with tetragonal tungsten bronze structures have been determined [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 39,40 . A detailed structural study indicated that the relaxor nature is always associated with incommensurate superlattice modulation.…”
Section: Introductionmentioning
confidence: 99%